1997
DOI: 10.1016/s0361-9230(97)00276-1
|View full text |Cite
|
Sign up to set email alerts
|

Borna Disease Virus and the Brain

Abstract: Viruses with the ability to establish persistent infection in the central nervous system (CNS) can induce progressive neurologic disorders associated with diverse pathological manifestations. Clinical, epidemiological, and virological evidence supports the hypothesis that viruses contribute to human mental diseases whose etiology remains elusive. Therefore, the investigation of the mechanisms whereby viruses persist in the CNS and disturb normal brain function represents an area of research relevant to clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 206 publications
0
67
0
Order By: Relevance
“…It has been reported that BDV infects a range of animal species worldwide (3), including China (4,5). BDV infects neurons in the limbic system, and primarily in the hippocampus and the cortex, which has wide spread connections to diverse cortical areas (6). However, BDV infection is restricted to areas of the rat brain that are responsible for intensive neurodegeneration in newborn Sprague-Dawley rats, indicating that the function of immature neural cells is impaired by BDV (7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that BDV infects a range of animal species worldwide (3), including China (4,5). BDV infects neurons in the limbic system, and primarily in the hippocampus and the cortex, which has wide spread connections to diverse cortical areas (6). However, BDV infection is restricted to areas of the rat brain that are responsible for intensive neurodegeneration in newborn Sprague-Dawley rats, indicating that the function of immature neural cells is impaired by BDV (7).…”
Section: Introductionmentioning
confidence: 99%
“…Both host and viral factors contribute to a variable period of incubation and heterogeneity in the symptoms and pathology associated with BDV infection (14,16,29,42,44). BDV provides an important model for the investigation of both immune-mediated pathological events associated with virus-induced neurological disease and mechanisms whereby noncytolytic viruses induce neurodevelopmental and behavioral disturbances in the absence of inflammation (15,18,41). Moreover, serological data and molecular epidemiological studies suggest that BDV, or a BDV-like virus, can infect humans and that it might be associated with certain neuropsychiatric disorders (17,24), which further underscores the interest in understanding the mechanisms underlying BDV persistence in the CNS and its effect on brain cell functions.…”
mentioning
confidence: 99%
“…Moreover, serological data and molecular epidemiological studies indicate that BDV can infect humans and might be associated with certain neuropsychiatric disorders (Billich et al, 2002;Carbone, 2001;Planz et al, 2002;Richt et al, 1997;Richt & Rott, 2001;Rott & Becht, 1995; Staeheli et al, 2000). Both virus and host factors contribute to a variable period of incubation, as well as significant heterogeneity, in the symptoms and pathology associated with BDV infection (Gonzalez-Dunia et al, 1997;Hatalski et al, 1997;Ikuta et al, 2002;Richt et al, 1997;Rott & Becht, 1995; Staeheli et al, 2000).BDV is an enveloped virus with a non-segmented, negativestranded RNA genome. Its genome is about 8?9 kb long, the smallest among known negative-stranded RNA viruses, and has an organization similar to that of other mononegaviruses (de la Torre, 1994;Schneemann et al, 1995).…”
mentioning
confidence: 99%